69.4k views
3 votes
Recursive formula for this geometric sequence, -125, -25, -5, -1

User Gustyn
by
5.5k points

2 Answers

7 votes

Answer:


a_n= (1)/(5) \cdot a_(n-1) \\ a_n= - 125

Explanation:

The given geometric sequence is:

-125, -25, -5, -1

We want to find a recursive formula for the given geometric sequence.

The first term of this sequence is


a_1=-125

The common ratio is


r = ( - 1)/( - 5) = (1)/(5)

The recursive definition is given by:


a_n=r\cdot a_(n-1)

We substitute the ratio to get:


a_n= (1)/(5) \cdot a_(n-1) \\ a_n= - 125

User Darkfrog
by
5.9k points
0 votes

Answer:

Recursive formula for this geometric sequence, -125, -25, -5, -1 will be:


a_n=-125\left((1)/(5)\right)^(n-1) where
a_1=-125

Explanation:

As we know that when we define a sequence by describing the relationship between its successive terms, it means we are defining the sequence recursively.

Given that,

-125, -25, -5, -1


\mathrm{Compute\:the\:ratios\:of\:all\:the\:adjacent\:terms}:\quad \:r=(a_(n+1))/(a_n)


(-25)/(-125)=(1)/(5),\:\quad (-5)/(-25)=(1)/(5),\:\quad (-1)/(-5)=(1)/(5)


\mathrm{The\:ratio\:of\:all\:the\:adjacent\:terms\:is\:the\:same\:and\:equal\:to}


r=(1)/(5)


\mathrm{The\:first\:element\:of\:the\:sequence\:is}


a_1=-125


a_n=a_1\cdot r^(n-1)


\mathrm{Therefore,\:the\:}n\mathrm{th\:term\:is\:computed\:by}\:


a_n=-125\left((1)/(5)\right)^(n-1)

As the recursive formula makes us able to find the next term in the sequence from the proceeding term by multiplying the preceding term by r.

Therefore,

Recursive formula for this geometric sequence, -125, -25, -5, -1 will be:


a_n=-125\left((1)/(5)\right)^(n-1) where
a_1=-125

User James Thigpen
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.